Customer value co-creation behaviour in fitness centres: how does it influence customers' value, satisfaction, and repatronage intention?. Issue 1 (4th May 2019) - Chiu, Weisheng; Won, Doyeon; Bae, Jung-sup
ABSTRACT: The purposes of this study were to propose a conceptual model and investigate the relationship between customer value co-creation behaviour (CVCB), customer value, satisfaction, and repatronage intention in the participation sport setting. Data were collected from 388 fitness club users in Taipei using a survey questionnaire and were analysed using structural equation modelling to examine the relationships between study variables. The results showed that CVCB has a positive influence on customer value and satisfaction, which in turn has positive influences on repatronage intention. Besides, the perceived value has a positive influence on satisfaction. Although a direct influence of CVCB on repatronage intention was not found, an indirect influence of customer citizenship behaviour through perceived value and satisfaction on repatronage intention was revealed. The findings of this study encourage managers of fitness centres to vigorously encourage customers to participate in the process of value co-creation.